Biosynthesis of poly-3-hydroxybutyrate from grass silage by a two-stage fermentation process based on an integrated biorefinery concept - Schwarz, Dominik; Schoenenwald, Amelie K J; Dörrstein, Jörg; Sterba, Jan; Kahoun, David; Fojtíková, Pavla; Vilímek, Josef; Schieder, Doris; Zollfrank, Cordt; Sieber, Volker (Bioresource technology, 2018)
Grass silage as a renewable feedstock for an integrated biorefinery includes nutrients and carbon sources directly available in the press juice (PJ) and in lignocellulosic saccharides from the plant framework. Here, a novel two-stage fed-batch fermentation process for biosynthesis of poly-3-hydroxybutyrate (PHB) by Cupriavidus necator DSM 531 is presented. For bacterial growth, nutrient-rich PJ was employed as a fermentation medium, without any supplements. Saccharides derived from the mechano-enzymatic hydrolysis of the press cake (PC) were subjected to a lactic acid fermentation process, before the fermentation products were fed into the polymer accumulation phase. By combination of pH-stat feeding and cell recycling, the PHB content in 22 g L-1 total-dry cells reached 39% after 32 h of cultivation. Using mimicked hydrolyzate of diluted PJ artificially supplemented with glucose and xylose, the resulting cell dry weight of 21 g L-1 contained 42% PHB.
Keywords: Green biorefinery; Bioreactors; Poly-3-hydroxybutyrate; Poaceae; Cupriavidus necator; Grass silage; siláž; Fermentation; fermentace; polyestery; Hydroxybutyrates; hydroxybutyráty; Silage; bioreaktory; Polyesters; Lactic acid fermentation; lipnicovité